Tathbiq al-Thariqah al-Ihaiyyah fi Ta’lim al-Lughah al-Arabiyyah fi Indunisiya - Aflisia, Noza; Hidayat, Rahmad; Yasmar, Renti; Wanto, Deri (Institut Agama Islam Negeri Curup, 2021)
This paper describes the application of the suggestopedia method in learning Arabic. This is a library research. The sources of data related to the suggestopedia method are taken from various books and scientific articles from various journals. The data collection technique is to review books and journals. The data obtained are then processed by collecting data regarding the suggestopedia method through various sources and literature, identifying and understanding the characteristics of Arabic learning, analyzing the substance of the suggestopedia method to be applied in Arabic learning, and drawing conclusions. The results of the study show that learning the language in a pleasant atmosphere can contribute a lot to the effectiveness of learning Arabic. The basic things that should not be forgotten in this method are six components, such as teacher authority, infantilization, multiple learning resources, intonation, rhythm, and relaxed attitude. Students learn not only from the materials taught but also from the environment. The double advantages obtained are that students gain language skills and at the same time enjoy life. This atmosphere is supported by intonation, rhythm, and a relaxed attitude that can relieve boredom of the lessons given. Students' minds are made as calm and relaxed as possible so as to stimulate the nerves, and then the material can be easily accepted and maintained in the long run.